Fatty Acid Dietary Supplements in Treatment of Developmental Coordination Disorder and ADHD - J Gordon Millichap (Pediatric Neurology Briefs)
The effects of dietary supplementation with fish oil and evening primrose oil (in a ratio of 80% to 20%) compared to placebo were assessed in a randomized, controlled trial in 117 children with developmental coordination disorder (DCD), aged 5-12 years, at the University of Oxford, UK.